Relationship of dynamic response of the head impact with time lost from concussions in elite hockey players - Janie, C. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: In elite hockey, it is reported that the incidence of concussions is 5.8 injuries per 100 players (1). Most players return to play within 10 days, yet some require a longer recovery which may take months (1). Concussive events can be studied using biomechanics in an effort to identify differences in impact mechanism between short and long recovery times. This could help sports medical teams to develop an accurate prognostic tool to ensure a player`s safety. The purpose of this study was to investigate the relationship between dynamic response of the head impact and recovery time. Methods: A search for videos of elite ice hockey players struck to the head was performed on the Internet using strict criteria to allow for physical reconstruction. A helmeted Hybrid III headform equipped with nine single-axis accelerometers with a 3-2-2-2 array was struck three times at three velocities (calculated velocity, ± 5 %) for a total of nine impacts. Shoulder impacts were reconstructed using a pneumatic piston while elbow impacts were reconstructed using two swinging pendulums. Results: Three events resulting in concussion lasting less than 10 days and five events resulting in concussion lasting more than one month were reconstructed. Mean peak linear acceleration was 24 ± 7 g for the short recovery time and 22 ± 13 g for the long recovery. Mean peak angular acceleration was 3.1 ± 0.7 krad/s2 for the short recovery time and 2.7 ± 0.6 krad/s2 for the long recovery time. No significant difference was found between the two groups. Discussion: The results suggest that dynamic response of the head upon impact is not an influencing factor on the duration of recovery time in the cases included in this study. Research suggests that the explanation for inter-individual differences in concussion recovery time is likely more physiological such as number and severity of previous concussions, age, sex, and intrinsic factors such as morphology of the cranial vasculature and differences in cerebral metabolic factors, as opposed to a characteristic of the force experienced by the head itself (2). The data presented in this study supports this hypothesis. The small sample size and the specificity of the inclusion criteria are limitations that need to be considered when considering the results in this study.